Hazard characterization of the mycotoxins enniatins and beauvericin to identify data gaps and improve risk assessment for human health - Anne-Cathrin Behr; Christiane Kruse Fæste; Amaya Azqueta; Ana M. Tavares; Anastasia Spyropoulou; Anita Solhaug; Ann-Karin Olsen; Ariane Vettorazzi; Birgit Mertens; Bojana Zegura; Camille Streel; Dieynaba Ndiaye; et al. (Archives of Toxicology, 2025)
Enniatins (ENNs) and beauvericin (BEA) are cyclic hexadepsipeptide fungal metabolites which have demonstrated antibiotic, antimycotic, and insecticidal activities. The substantial toxic potentials of these mycotoxins are associated with their ionophoric molecular properties and relatively high lipophilicities. ENNs occur extensively in grain and grain-derived products and are considered a food safety issue by the European Food Safety Authority (EFSA). The tolerable daily intake and maximum levels for ENNs in humans and animals remain unestablished due to key toxicological and toxicokinetic data gaps, preventing full risk assessment. Aiming to find critical data gaps impeding hazard characterization and risk evaluation, this review presents a comprehensive summary of the existing information from in vitro and in vivo studies on toxicokinetic characteristics and cytotoxic, genotoxic, immunotoxic, endocrine, reproductive and developmental effects of the most prevalent ENN analogues (ENN A, A1, B, B1) and BEA. The missing information identified showed that additional studies on ENNs and BEA have to be performed before sufficient data for an in-depth hazard characterisation of these mycotoxins become available.